Intravenous Leiomyoma with Intracardiac Extension: A Rare Late Presentation After Hysterectomy - Jaiswal, Lokesh Shekher; Pandit, Narendra; Prasad, Jagat Narayan; Pandey, Naveen Kumar (Nepalese Heart Journal, 2020)
Intravenous leiomyoma is a rare, benign smooth muscle tumor arising from intrauterine venules or the myometrium. It can rarely present as intracardiac mass long after hysterectomy. In this case report we describe a 40-year-old female with previous history of hysterectomy, presenting with an intracardiac mass which was successfully managed with single stage tumor resection under cardiopulmonary bypass. Subsequent histopathology showed features of leiomyoma. The diagnosis of intravenous leiomyoma with cardiac extension should be kept in a female patient presenting with intracardiac mass with previous history of myomectomy or hysterectomy.